Pengembangan Bahan Ajar bagi SEKAMI Di Stasi Santo Paulus Luwuk Bunter Paroki Santo Joan Don Bosco Sampit - Dini Nopita Sari; Paulina Maria Ekasari Wahyuningrum; Silvester Adinuhgra (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
This study aims to determine the feasibility of the developed teaching materials and to describe the results of trials of SEKAMI teaching materials for SEKAMI assistants and children at the Luwuk Bunter Station. This research is supported by the problems researchers experience when carrying out KKN at the station. The teaching materials used were less able to be followed by local facilitators and less attractive to SEKAMI children. This type of research is developmental research. The development of SEKAMI teaching materials uses the ADDIE development stage. The feasibility of teaching materials was assessed in 2 stages by two validators who worked as SEKAMI children's companions at St. Maria Palangkaraya. After the revision, trials were carried out on SEKAMI companions and children at the Luwuk Bunter Station.